The influence of age in women in visuo-spatial memory in reaching and navigation tasks with and without landmarks. (25th September 2018) - Perrochon, A.; Mandigout, S.; Petruzzellis, S.; Soria Garcia, N.; Zaoui, M.; Berthoz, A.; Daviet, J.C.
Highlights: Aging seems to be associated with a decline of spatial memory and navigation capabilities. No difference was found in WM performance between reaching and navigation spaces. Older women have poorer navigational skills when the environment contains landmarks. No impact of the presence of landmarks on route learning in young women subjects. Abstract: Spatial memory and navigation capabilities tend to decline in normal aging, but few studies have assessed the impact of landmarks on route learning in a large-scale environment. The objectives were to examine age-related effects on visuo-spatial working memory capabilities in various environments and to determine the impact of landmarks in navigation skills in normal aging. 42 young women (23.6 ± 4.9 years) and 37 older women (70.7 ± 4.7 years) with no cognitive impairment have performed three visuo-spatial working memory tests: one in reaching space (computerized Corsi-Block-Tapping test) and two in locomotor navigation space (a condition without landmarks: Virtual Walking Corsi Test and a condition with landmarks: Virtual Room Walking Test). A two-way mixed ANOVA test showed that the young subjects performed better in all conditions than older subjects. The performance in visuo-spatial working memory thus decreases with age. Visuo-spatial working memory performances were identical in reaching and navigation spaces for both groups. The integration of landmarks into a navigational task decreases performance in older women, while this performance is not altered in younger women.